POSTAWY POLAKÓW WOBEC KOŚCIOŁA KATOLICKIEGO – ANALIZA SOCJOLOGICZNA - Mariański, Janusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In this article, first, we draw attention to the understanding of the Church in the consciousness of Polish Catholics, and their trust in the Church. Next, we discuss the activities of the Catholic Church in society, its involvement in political affairs, and the presence of religious symbols in the public sphere. The issue of attitudes of Polish people towards the Church is examined from the sociological point of view, taking into account the selected results of public opinion polls and sociological research. Since our study of the Church is sociological in nature, we – of course – do not analyze theological dimensions (the Church as the Mystical Body, the Church as the People of God). From a theological point of view, the external aspects of the Church are of secondary importance, whereas a sociologist can describe, interpret and explain the external and social dimensions of the Church